Endogenous Repo Cycles - Makoto Watanabe; Vyacheslav Arbuzov; Yu Awaya; Hiroki Fukai (Tinbergen Institute, 2019)
This paper presents a simple and tractable equilibrium model of repos, where collateralized credit emerges under limited commitment. We show that even if there is no time variation in fundamentals, repo markets can fluctuate endogenously over time. In our theory, repo market fragilities are associated with endogenous fluctuations in trade probabilities, collateral values, and debt limits. We show that the collateral premium of a durable asset will become the lowest right before a recession and the highest right after the recession and that secured credit is acyclical.
Keywords: E30; E50; C73; 330; collateral; search; endogenous credit market fluctuations